(untitled) (Journal of Hama University, 2024)
This study was conducted in the Bahlouliyeh district of Latakia Governorate during the 2022 and 2023 agricultural seasons on lemon trees of the “Mayer” variety, 15 years old and planted at a distance of 4*4 m. With the aim of studying the effect of foliar feeding with nutrients (N, K, B) and gibberellic acid (GA3) on some vegetativegrowth indicators of Meyer lemon trees. Four chemical compounds were used in foliar spraying: urea, potassium sulfate, boron, and gibberellic acid, individually and in combination, at different concentrations (2.5 g/l, 1.5 g/l, 200ppm, 20ppm), respectively. The results showed that the spraying treatment with the four compounds combined (GA3, N, B, and K) was superior to all the studied treatments in tree crown size with an increase rate of (43.77%) and (43.15%) for both the first and second season, respectively, compared to the control that did not The percentage increase in tree crown size exceeds (17.84%) and (12.30%) for both seasons. The results showed that the spray treatment with the four compounds combined (GA3, N, B, K) and the spray treatment with urea + boron together outperformed all the treatments studied in terms of stem circumference with an increase rate of 7.59%, 7.20%, followed by the foliar spray treatment with boron + K2SO4 with an increase rate. 6.8%. The results also showed that the spray treatment with the four compounds combined, the spray treatment with urea + boron, and the foliar spray treatment with boron + K2SO4 ((T9) together was significant to all the treatments studied with a total chlorophyll percentage that reached (64.88, 63.65, 64.39) SPAD compared to the control (58.10) SPAD.